2002
DOI: 10.1002/neu.10133
|View full text |Cite
|
Sign up to set email alerts
|

Effect of reduced impulse activity on the development of identified motor terminals in Drosophila larvae

Abstract: In Drosophila larvae, motoneurons show distinctive differences in the size of their synaptic boutons; that is, axon 1 has type Ib ("big" boutons) terminals and axon 2 has type Is ("small" boutons) terminals on muscle fibers 6 and 7. To determine whether axon 1 develops large boutons due to its high impulse activity, we reduced impulse activity and examined the motor terminals formed by axon 1. The number of functional Na(+) channels was reduced either with the nap(ts) mutation or by adding tetrodotoxin (TTX) t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 35 publications
0
25
0
Order By: Relevance
“…Changes in the size and morphology of the Drosophila neuromuscular junction have been shown to occur as a result of perturbations in both presynaptic activity (Lnenicka et al, 2003;Mosca et al, 2005) and regulatory signaling (Packard et al, 2002;Keshishian and Kim, 2004;Ruiz-Canada and Budnik, 2006). However, many other perturbations of synaptic function do not have these effects, including viable mutations in synaptotagmin, syntaxin and SNAP-25 (DiAntonio and Schwarz, 1994;Schulze et al, 1995;Vilinsky et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Changes in the size and morphology of the Drosophila neuromuscular junction have been shown to occur as a result of perturbations in both presynaptic activity (Lnenicka et al, 2003;Mosca et al, 2005) and regulatory signaling (Packard et al, 2002;Keshishian and Kim, 2004;Ruiz-Canada and Budnik, 2006). However, many other perturbations of synaptic function do not have these effects, including viable mutations in synaptotagmin, syntaxin and SNAP-25 (DiAntonio and Schwarz, 1994;Schulze et al, 1995;Vilinsky et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Both hyper-and hypoexcitability alter the development of the Drosophila NMJ (6,7,9,60). Electrical activity is also essential for regulating neuromuscular signaling through homeostatic feedback mechanisms that influence both presynaptic transmitter release and postsynaptic transmitter sensitivity (10,11,47).…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms that maintain synaptic homeostasis have been extensively studied, and clever genetic manipulations have shown that both anterograde (from motoneuron to muscle) and retrograde signaling (from muscle to motoneuron) is required for appropriate growth and function of the NMJ (Budnik et al, 1990;Jarecki and Keshishian, 1995;Petersen et al, 1997;DiAntonio et al, 1999;Baines et al, 2001;Paradis et al, 2001;Lnenicka et al, 2003). Over the past few years, two classical morphogens have been identified as essential regulators of synaptic growth.…”
Section: Synaptogenesis: Initial Establishment and Synapse Maturationmentioning
confidence: 99%